1999
DOI: 10.1046/j.1523-1755.1999.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Nanobacteria: An infectious cause for kidney stone formation

Abstract: We propose that kidney stone formation is a nanobacterial disease analogous to Helicobacter pylori infection and peptic ulcer disease. Both diseases are initiated by bacterial infection and subsequently endogenous and dietary factors influence their progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
162
2
9

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(177 citation statements)
references
References 22 publications
(7 reference statements)
4
162
2
9
Order By: Relevance
“…Deficiencies in several macromolecules that inhibit crystallization of matrix in urine have also been suggested as a contributory factor to calculogenesis (Griffin 1998, Atmani & Khan 1999. Uroliths have been linked to nanobacterial infection but dietary factors influence their progression (Ciftcioglu et al 1999).…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…Deficiencies in several macromolecules that inhibit crystallization of matrix in urine have also been suggested as a contributory factor to calculogenesis (Griffin 1998, Atmani & Khan 1999. Uroliths have been linked to nanobacterial infection but dietary factors influence their progression (Ciftcioglu et al 1999).…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…Proteins that have crystal binding affinity could play an important role in mediating the earliest events in both atherosclerosis and KS formation (34). There are also studies that investigated nanobacteria, which are supposed to be an etiological factor for both KSs and calcified human arteries (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…They are isolated in pure culture of lesion (nanobacteria are detected in demineralization of stones in 1N HCl). 16 3. Inoculation of nanobacteria reproduce the pathologic calcification (Garcia Cuerpo et al found that translumbar, percutaneous intrarenal injection of calcifying nanoparticles that is isolated from kidney stones into rats resulted in kidney stone formation).…”
Section: Nanobacteria: Fact or Fictionmentioning
confidence: 99%
“…40 On screening of demineralized kidney stones using a double staining method, scanning electron microscopy and specific culture method 93.1% stones contain nanobacteria and after compilation of all the assay results 70 out of 72 (97.2%) renal stones were positive for nanobacteria. 16 Moreover, the risk of urolithiasis recurrence may be reduced with antinanobacterial therapy. 41 …”
Section: Nanobacteria and Renal Stonesmentioning
confidence: 99%